2019
DOI: 10.1007/s10295-019-02161-x
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic study of effects of flow velocity and nutrient concentration on biofilm accumulation and adhesive strength in the flowing and no-flowing microchannels

Abstract: Biofilm accumulation in porous media can cause pore plugging and change many of the physical properties of porous media. Engineering bioplugging may have significant applications for many industrial processes, while improved knowledge on biofilm accumulation in porous media at porescale in general has broad relevance for a range of industries as well as environmental and water research. The experimental results by means of microscopic imaging over a T-shape microchannel clearly show that increase in fluid velo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(30 citation statements)
references
References 55 publications
2
28
0
Order By: Relevance
“…While hydrodynamic conditions can significantly affect bacterial behavior on surfaces and subsequent biofilm formation, the influence of dynamic conditions on bacterial adhesion and biofilm formation has been often neglected. According to previous literature, biofilm growth can be facilitated under fluid conditions (Thomen et al, 2017;Liu et al, 2019). A study done by Hou et al (2018) showed that shear flow enhances biofilm formation by increasing the EPS production and strength of the EPS-matrix in S. aureus.…”
Section: Environmental Factors Fluid Dynamicsmentioning
confidence: 90%
“…While hydrodynamic conditions can significantly affect bacterial behavior on surfaces and subsequent biofilm formation, the influence of dynamic conditions on bacterial adhesion and biofilm formation has been often neglected. According to previous literature, biofilm growth can be facilitated under fluid conditions (Thomen et al, 2017;Liu et al, 2019). A study done by Hou et al (2018) showed that shear flow enhances biofilm formation by increasing the EPS production and strength of the EPS-matrix in S. aureus.…”
Section: Environmental Factors Fluid Dynamicsmentioning
confidence: 90%
“…Our results are in accordance with biofilm formation studies with Acinetobacter baumannii , where higher nutrient concentrations decreased biofilm accumulation and poor nutrient media increased biofilm production [ 20 ]. Studies on the influence of nutrient supply on biofilm formation in a microchannel system by Liu et al demonstrated a strong nutritional effect on biofilm morphology [ 21 ]. With high nutrient load, the formation of thick, but loose structures was observed, that are highly sensitive to shear stress.…”
Section: Discussionmentioning
confidence: 99%
“…[209][210][211] They remain, nevertheless, very important since the mass of carbon of all these microorganisms would be 245 to 385 times higher than the mass of carbon represented by the whole humanity. These intraterrestrial microorganisms can modify the microporous network through three main mechanisms: (i) the modification of the mineral surface properties leading to wettability alteration within the porous structures 212,213 ; (ii) the microsystem bioclogging with biomass accumulation, contributing to a decrease in permeability 214,215 and combined modification of the mineral surface properties, the geochemistry, and the overall hydrodynamic of the porous media 216 ; and (iii) the precipitation biominerals, mainly carbonates, causing also clogging in the porous network. [217][218][219] It has also been demonstrated at the Ketzin geological storage site (CO 2 SINK project) that the metabolic activity of the sulfatereducing microorganisms clogged the porosity of the aquifer nearby the well Ktzi 201 because of the sulfide generated combining with dissolved iron to form iron sulfides.…”
Section: Biogeochemical Effectsmentioning
confidence: 99%